2005
DOI: 10.1002/jssc.200400086
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the field of monolithic stationary phases for capillary electrochromatography

Abstract: This review summarizes the contributions to the rapidly growing area of monolithic columns based on both silica and synthetic polymers for capillary electrochromatography and chip electrochromatography, with a focus on those published during the year 2004. A wide variety of both modified approaches to the "old" monoliths and new monoliths have been reported despite the very short period of time covered. This demonstrates that monolithic stationary phases have become a well-established format in the field of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
143
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(152 citation statements)
references
References 113 publications
3
143
0
6
Order By: Relevance
“…It can be extremely useful in applications where high column efficiency can make a big difference. One example is the proteomic separation of complex peptide and/or glycan mixtures, followed by MS detection (20,21). CEC separations of proteins and peptides are difficult to perform because of the ionizable nature of these compounds.…”
Section: Capillary Electrochromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be extremely useful in applications where high column efficiency can make a big difference. One example is the proteomic separation of complex peptide and/or glycan mixtures, followed by MS detection (20,21). CEC separations of proteins and peptides are difficult to perform because of the ionizable nature of these compounds.…”
Section: Capillary Electrochromatographymentioning
confidence: 99%
“…Nevertheless, this distinction was recently challenged by highly efficient separations of midsized peptides in silica-based monoliths (60). Similarly, CEC with polymeric monoliths was used to achieve excellent separation of small molecules (21). In the near future, we expect more studies of the optimization and application of silica-and polymer-based monolithic columns for separating small and large molecules.…”
Section: Misconceptions and Real Problemsmentioning
confidence: 99%
“…They therefore exhibit different advantages and disadvantages. A number of review articles have been published in the last decade describing progresses on their preparations, properties, and applications [12][13][14][15][16][17][18]. It can be easily found that the problems of both the swelling or shrinkage of organic monoliths in some solvents and the tedious fabrication procedures of the silica-based monoliths always encumber the researchers and limit the applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, monolithic capillary columns have gained increasing attention in CEC because of their advantages over other kinds of columns, such as no need to prepare frits, fast mass transfer and high phase ratio, etc. [4,5]. Depending on the nature of materials, monolithic columns can be classified into two major categories: the silica-based monolithic column [6] and the organic polymer-based monolithic column [7].…”
Section: Introductionmentioning
confidence: 99%